Evaluasi Media Game-Based Learning Berbasis Zep Quiz pada Mata Pelajaran Pendidikan Agama Islam: Evaluation Of Game-Based Learning Media Based on Zep Quiz in Islamic Education Subject - Dian Rustyawati; Asma Hidayatul Hasanah (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2026)
The development of the internet, technology, and information has forced the education sector to adapt to these changes to graduate students who are well-prepared for future needs. Currently, there are various platform options for learning media, one of which is Zep Quiz. This study aims to evaluate the use of Zep Quiz as a learning medium for Islamic Studies. The research method employed is Research and Development using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The results of the study indicate that the game-based learning evaluation tool using Zep Quiz has a validity score of 0.90, a practicality score of 0.95, and an effectiveness score of 0.87. Therefore, the Zep Quiz evaluation tool is suitable for use, as it is highly valid, practical, and effective